Comparison of Management Information System (MIS) and Decision Support System (DSS) and its role in the decision-making process of managers of Economic Affairs and Finance of Zahedan - Abdolali Keshtegar; Nadia Vakili (International Review of Management and Marketing, 2018)
Nowadays, the variety of information systems and their advantages are sometimes accompanied by common and interfering concepts and goals. This variety and dispersion have created complexity and instability in decision-making of organizations mangers and IT development plans. Overall to solve this complexity, information systems are defined in two broad classes: specific connection with the operational field and in general connection with the operational field. MIS and DSS systems are among the systems in general connection with the operational field, each of which plays a decisive role in the organizational hierarchy and decision-making process of the mangers. MIS system brings about the information needed to manage an organization, and DSS provides data, models, and analysis tools to help adopt decisions in non-routine cases in the organization.  After discussion on decision-making process based on each concept, this study described its characteristics, relationships, and communication of each concept for the decision-making process. The results of regression analysis of data from 20 questionnaires received from the managers of Economic Affairs and Finance (EAF) in Zahedan showed that MIS and DSS have a significant relationship with the decision-making process of managers and that rational decision-making process as the intermediary variable inferred and explained this effect.